Analyzing ethical practices in the public healthcare sector using fuzzy cognitive mapping - Abrantes, J.; Ferreira, F.; Zopounidis, C.; Pereira, L.; Meidute-Kavaliauskiene, I. (Journal of Multi-Criteria Decision Analysis, 2022)
This study focused on some of the most important aspects of ethics in the healthcare industry and examined the relevance of the system created to evaluate ethical healthcare practices in the public sector. The research included developing a conceptual model representing variables that influence ethics in public healthcare services in Portugal, using fuzzy cognitive mapping to facilitate the identification of the most significant variables. This method is a well-established decision problem-structuring tool that allows experts to define cause-and-effect relationships between variables and make decisions. The insights obtained were generated in face-to-face group meetings with experts in the public healthcare sector, showing that professional profiles, management, team relationships, external factors, equity principles, and respect are among the most relevant determinants of ethical healthcare. That is, these criteria are the most commonly applied standards in analyses of ethical practices in public healthcare services. The resulting assessment framework and its applicability were validated by both the panel of experts and the chairperson of the board of directors of S. Francisco Xavier Hospital in Lisbon, Portugal. The advantages and limitations of the analysis developed in this study are also discussed.